Built environment and micro-mobility: A systematic review of international literature - Yushan Zhang; Dena Kasraian; Pieter van Wesemael (Journal of Transport and Land Use)
Recent innovations in business models and technology have brought out new mobility systems, including shared and electric micro-mobility. A rapidly expanding strand of literature mirrors the micro-mobility’s exponential growth and popularity. While many studies analyze micro-mobility from operations, management and user perspectives, fewer works investigate the micro-mobility and built environment (BE) relationship. This paper systematically reviews the descriptive and empirical studies that investigate this relationship. It analyzes whether, similar to other transportation modes, micro-mobility (e.g., bike-sharing schemes and e-bikes/e-scooters) can potentially influence three BE aspects: urban design, land use, and transportation system. Furthermore, it outlines the recommended changes in the BE to support the micro-mobility and/or enhance the quality of the environment for non-users. This paper investigates the BE and micro-mobility relation at the three levels of node (e.g., the emergence of docking stations and parking stops), link (e.g., the street-level conflicts with walking/cycling/vehicle lanes) and network (e.g., infrastructure network creation and catchment area shifts). In addition, this relation is explored over time, based on the development stage of micro-mobility, the BE aspect (urban design, land use, or transport system), and spatial context (urban or rural). The findings are relevant for urban and transport planners, designers, researchers, policy makers and public authorities. They contribute to a much-needed evidence base for effective design and policy recommendations to accommodate micro-mobility in the BE to achieve a safe and inclusive public space.